2018
DOI: 10.3389/fnmol.2018.00420
|View full text |Cite
|
Sign up to set email alerts
|

Parabrachial Neurons Promote Behavior and Electroencephalographic Arousal From General Anesthesia

Abstract: General anesthesia has been used clinically for more than 170 years, yet its underlying mechanisms are still not fully understood. The parabrachial nucleus (PBN) in the brainstem has been known to be crucial for regulating wakefulness and signs of arousal on the cortical electroencephalogram (EEG). Lesions of the parabrachial complex lead to unresponsiveness and a monotonous high-voltage, and a slow-wave EEG, which are the two main features of general anesthesia. However, it is unclear whether and how the PBN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 53 publications
8
65
0
Order By: Relevance
“…Abbreviations: 3 V, third ventricle; AQ, cerebral aqueduct; CMT, central medial nucleus of thalamus; DR, dorsal raphe nucleus; fx, fornix; LD, laterodorsal nucleus of thalamus; LDT, laterodorsal tegmental nucleus; LGN, lateral geniculate nucleus of thalamus; LP, lateral posterior nucleus of thalamus; MD, mediodorsal nucleus of thalamus; ml, medial lemniscus; MR, median raphe nucleus; PAG, periaqueductal gray; PH, posterior hypothalamus; PSV, principal sensory nucleus of trigeminal nerve; PV, paraventricular nucleus of thalamus; RE, nucleus reuniens of thalamus; RF, reticular formation; RM, raphe magnus, RPC, reticularis pontis caudalis; RT, reticular nucleus of thalamus; V, motor nucleus of trigeminal nerve; VB, ventrobasal complex of thalamus; VM, ventromedial nucleus of thalamus; VTN, ventral tegmental nucleus; ZI, zona incerta anesthesia, Muindi et al (2016) described enhanced levels of c-fos expression in PB during the (passive) emergence from isoflurane anesthesia, and further reported that PB stimulation produced arousal and return of the righting reflex during continuous isoflurane administration. Consistent with this, Luo et al (2018) demonstrated that PB activity was suppressed during propofol or isoflurane anesthesia and strongly enhanced with emergence from anesthesia. Further, chemogenetic PB activation significantly shortened the recovery time from these GAs (Luo et al, 2018).…”
Section: Gas Act On Sleep/wake Control Systems: the Arousal/wakefulsupporting
confidence: 66%
See 1 more Smart Citation
“…Abbreviations: 3 V, third ventricle; AQ, cerebral aqueduct; CMT, central medial nucleus of thalamus; DR, dorsal raphe nucleus; fx, fornix; LD, laterodorsal nucleus of thalamus; LDT, laterodorsal tegmental nucleus; LGN, lateral geniculate nucleus of thalamus; LP, lateral posterior nucleus of thalamus; MD, mediodorsal nucleus of thalamus; ml, medial lemniscus; MR, median raphe nucleus; PAG, periaqueductal gray; PH, posterior hypothalamus; PSV, principal sensory nucleus of trigeminal nerve; PV, paraventricular nucleus of thalamus; RE, nucleus reuniens of thalamus; RF, reticular formation; RM, raphe magnus, RPC, reticularis pontis caudalis; RT, reticular nucleus of thalamus; V, motor nucleus of trigeminal nerve; VB, ventrobasal complex of thalamus; VM, ventromedial nucleus of thalamus; VTN, ventral tegmental nucleus; ZI, zona incerta anesthesia, Muindi et al (2016) described enhanced levels of c-fos expression in PB during the (passive) emergence from isoflurane anesthesia, and further reported that PB stimulation produced arousal and return of the righting reflex during continuous isoflurane administration. Consistent with this, Luo et al (2018) demonstrated that PB activity was suppressed during propofol or isoflurane anesthesia and strongly enhanced with emergence from anesthesia. Further, chemogenetic PB activation significantly shortened the recovery time from these GAs (Luo et al, 2018).…”
Section: Gas Act On Sleep/wake Control Systems: the Arousal/wakefulsupporting
confidence: 66%
“…Consistent with this, Luo et al (2018) demonstrated that PB activity was suppressed during propofol or isoflurane anesthesia and strongly enhanced with emergence from anesthesia. Further, chemogenetic PB activation significantly shortened the recovery time from these GAs (Luo et al, 2018).…”
Section: Gas Act On Sleep/wake Control Systems: the Arousal/wakefulsupporting
confidence: 66%
“…We also discovered that continuous isoflurane gradually inhibits the activity of cholinergic neurons in the induction period, and LORR occurred when the activity reduced to a certain level. However, for propofol anesthesia, we noticed that the injection of propofol causes a brief and slight activation of BF cholinergic neurons; this is likely on account of the direct stimulation of injection pain or signal transmission from other pain sensation-related brain regions (Yuan et al, 2016;Luo T. et al, 2018). In spite of this, the event of BF cholinergic neurons is rapidly and continuously inhibited during propofol anesthesia.…”
Section: Discussionmentioning
confidence: 86%
“…In this serial study, the data are presented as mean ± SEM. Sample size calculations of every step were based on our previous studies (Luo T. et al, 2018;Zhang et al, 2019). The changes in neuronal calcium signals of different anesthesia stages were analyzed using paired Student's t-tests.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…The NTS also projects to the parabrachial complex, which are nuclei located in the dorsolateral pons and surrounds the superior cerebellar peduncle. The parabrachial complex projects to areas of the brain involved in arousal including the thalamus, medial and lateral hypothalamus, and amygdala (316). Additionally, the NTS projects to the reticular formation, which are interconnected nuclei found thought the brainstem.…”
Section: Vagus Nerve and Cns Inflammationmentioning
confidence: 99%